Photoinduced, family-specific, site-selective cleavage of TIM-barrel proteins. - Floyd, N; Oldham, N; Eyles, C; Taylor, S; Filatov, D; Brouard, M; Davis, B (2009)
Nonenzymatic, chemical methods for the controlled cleavage of proteins at predictable sites in a site-specific manner are rare and of strong potential utility in clean, post-translational manipulation of protein structure for use in, for example, proteomics, sequencing, and tagged-protein production. Unprecedented photochemical, site-selective cleavage of a His-Trp (HW) motif in the GH1 family TIM-barrel proteins is observed upon exposure to 240-308 nm light to cleanly release N-terminal primary amide and C-terminal indolylenamide fragments. We also show that this photocleaveable motif can be transferred to fusion proteins for use in photoresponsive affinty purification. The presence of this motif in proteins found only in organisms that are not typically exposed to light raises the possibility of direct biological relevance for this new type of protein reaction.